Use of Novel Biological Agent in Severe Ulcerative Colitis with Poor Response to Initial Therapy: A Case Report - Abashesh Bhandari; Bhupendra Kumar Basnet (Journal of Nepal Medical Association, 2022)
Ulcerative colitis is a condition of chronic inflammation affecting the large intestine. The disease is typically characterized by periods of active inflammation alternating with periods of remission. For patients with moderate to severe ulcerative colitis, the first line for induction therapy options includes biologic agents (with or without an immunomodulator) or glucocorticoids. This case highlights the first successful case of ulcerative colitis treated with adalimumab with mesalamine and azathioprine. The patient was initially treated with mesalamine and azathioprine which did not result in significant clinical improvement but the addition of subcutaneous adalimumab showed a remarkable response with drastic improvement in just one year of treatment. Hence, adalimumab could be considered as an option in the management of severe cases in Nepal.